Pengaruh Pemahaman Regulasi, Persepsi Kemudahan Administrasi, dan Persepsi Kesederhanaan terhadap Kepatuhan Perpajakan dalam Skema KSO - Pramesti, Retta Farah; Priyono, Agus Puji (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi (Jebma), 2025)
Abstract: Jurnal Jebma is an Indonesian-language journal. Please write abstracts in Indonesian. An abstract should be written in one paragraph with the following sections:Background: Joint Operations (KSO) are increasingly being used in infrastructure and service projects in Indonesia, but tax compliance still faces challenges related to understanding regulations and administration. Therefore, this research is necessary.Method: This research used a quantitative survey method with a 1–5 Likert-scale questionnaire distributed to 259 respondents (academics, practitioners, and the general public). The data were analyzed using multiple linear regression after undergoing classical assumption testing, using instruments proven reliable and valid.Results: Understanding tax regulations (X1) and perceived ease of administration (X2) had a positive and significant effect on KSO tax compliance, while perceived simplicity of regulations (X3) had no significant effect; all three variables simultaneously had a significant effect.Conclusion: Increasing regulatory literacy and improving ease of administration, particularly through process digitization, are more important determinants of KSO tax compliance than perceived simplicity of regulations.